SecAdvise: A security mechanism advisor - Saliba, Rima; Babin, Gilbert; Kropf, Peter (: Springer-Verlag Berlin, 2002)
The proliferation of incompatible e-commerce systems applying different security technologies imposes difficult choices on all the concerned parties. In this context, the purpose of this research is to provide the necessary background to develop a security advisor (SecAdvise), which will make it possible to integrate the security mechanisms and the dynamic selection of the various mechanisms between several parties wishing to conduct business transactions safely. Such an advisor aims multiple goals: overcoming compatibility and interoperability problems, evaluating and reducing technological security risks, and enhancing trust.
, 2002